GERAKAN LINGKUNGAN DI JAWA MASA KOLONIAL (History Department, Semarang State University and Historian Society of Indonesia, 2014)
This article discusses the genesis of the environmental movement in Java during the Dutch colonial era. A number of studies voicing the importance of environmental protection and environment-related local wisdoms have appeared. But, little has been done to uncover the question of how the environmental movement developed and consolidated itself in Java. The neglect of environmental movement dimension causes a failure to transform cultural wisdoms and academic findings into powerful corrective force, useless like “weapon without soldier”. By emplyoing a historical method, this article aims at elaborating the genesis of environmental movement in Java, issues that were taken into focus in the movement and its real achievments during the Dutch colonial era. The argument is built on the basis of Dutch historical material sources in various forms especially archival materials, official and organisational publications, and complemetarily supported with relevant secondary sources. It is argued that the environmental movement in Java had European/Dutch elite as its major agent, evolved in line with the development of Western interests and understanding of colony functions in economic and non-economic terms, and made concret achievements in legal, orgsnizational-administrative, and practical terms. Key words: environmental movement, colonial era, JavaSejumlah kajian yang menyuarakan pentingnya pelestarian lingkungan dan nilai-nilai kearifan lokal terkait lingkungan memang banyak dihasilkan. Akan tetapi kajian-kajian yang ada belum secara sistematis mengkaji bagaimana gerakan lingkungan muncul dan mengonsolidasi diri termasuk di Jawa. Diabaikannya dimensi gerakan lingkungan membuat nilai-nilai kearifan budaya dan temuan-temuan akademis terkait lingkungan bagai “senjata tanpa tentara”. Melalui penggunaan metode sejarah, tulisan ini bertujuan mengkaji munculnya gerakan lingkungan di Jawa, isu-isu yang menjadi fokus perhatian dan capaian-capaian yang diraih gerakan lingkungan di Jawa pada masa kolonial. Argumentasi tulisan dibangun dengan memanfaatkan terutama sumber-sumber Belanda dalam beragam rupa termasuk arsip, publikasi resmi dan organisasi. Diargumentasikan bahwa gerakan lingkungan di Jawa pada masa kolonial memperlihatkan elite Eropa/Belanda sebagai agensinya, berevolusi seiring dengan perkembangan kepentingan dan pemahaman Barat atas fungsi koloni secara ekonomi dan non-ekonomi, serta mempunyai capaian-capaian konkret dalam aspek legal, organisatoris-administratif, dan praktis. Kata kunci: gerakan lingkungan, masa kolonial, Jawa,